Beneficial of Bioactive Compound of Rice Bran for Chicken’s Functional Feed - cecep hidayat; Elizabeth Wina; Soni Sopiyana (Indonesian Center for Animal Research and Development, 2021)
Rice bran is a feed ingredient as a result of the rice milling process which widely used as an energy source in the feed formulation in the chicken diet. Rice bran contains various nutrients such as oil, protein, carbohydrates (especially starch), beta-glucans, and pectins. Rice bran contains bioactive compounds that have positive effects on the chicken performance and health. Recently, rice bran’s bioactive compounds have been developed as a source of making functional feed. The objective of this study was to review the bioactive compounds in rice bran and their benefits in order to produce chicken’s functional feed. The results of the study showed that rice bran contains oryzanol as an important bioactive compound that has high antioxidant activity. Furthermore, other bioactive compound, lysolecithin, has an ability to reduce cholesterol content in blood, meat and eggs of chicken. Besides, rice bran extract is reported to exert antibacterial activity and has immunomodulator function. It was concluded that the bioactive compounds of rice bran is potential to be used as a substance for making functional feed for chickens.